Peran Guru PAI Dalam Meningkatkan Kualitas Membaca Al-Qur’an Peserta Didik Di SMA Bosowa Bina Insani Kota Bogor - Syahdatun Nisa Salsabila; Syarifah Gustiawati Mukri; Khaidir Fadil (Universitas Pahlawan Tuanku Tambusai, 2023)
Learning Islamic Religious Education is inseparable from the problems that occur during the process, one of which is the problem of the lack of quality of reading the Quran properly and correctly in students and weak awareness in getting used to reading the Quran in students. Therefore, the purpose of this study is to be able to determine the role of PAI teachers in improving the quality of students Quran readings and the process of improving students Quran readings at Bosowa Bina Insani High School in Bogor City. This research uses qualitative methods with a field research approach. The data used in this study were the results of observation, interviews, and documentation. The results of this study show that the role of PAI teachers in improving the quality of reading the Quran of students includes: as learning resources, facilitators, managers, demonstrators, guides, motivators, and evaluators. In the process of improving Quran reading at Bosowa Bina Insani High School Bogor City, applying peerteaching methods or peer tutors in PAI lessons on Quran material. Keywords: The Role of Teachers, Reading the Quran, Islamic Education